Formulasi Salep Ekstrak Ikan Gabus (Channa striata) dan Madu Kelulut (Heterotrigona itama) sebagai Antioksidan - Ely lisnawati; Wintari Taurina; Mohamad Andrie (Journal Syifa Sciences and Clinical Research, 2022)
Kelulut honey and snakehead fish extract have been demonstrated to improve wound healing, hence the two active components are combined in ointment formulations. Adeps lanae is a base that is included in the oil phase that undergo an oxidation process that causes rancidity in the ointment preparation, so in this study BHA and BHT antioxidants were added to suppress the oxidation process. The ointment was made with 5 concentrations consisting of 1 control group and 4 treatment groups which were given variations of BHA and BHT antioxidants. Organoleptic testing, homogeneity, adhesion, dispersion, protection, and acid numbers were all evaluated. SPSS 24 is used to test data related to adhesion, and dispersion. Results: The addition of antioxidants BHA and BHT based on acid number tests revealed that the higher the combination of antioxidants employed, the less the increase in acid numbers on day 28. The organoleptic test, homogeneity, protection, and adhesion on the preparation fulfilled the test criteria, whereas the adhesion test revealed significant differences in F1, F2, and F4 when compared to the control group. The optimum formula is F4, which fits the test parameters and has the minimum rise in acid number (9.22 mg KOH/g).